1968
DOI: 10.1063/1.1669814
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Transport Characteristics of Ultrafine Capillaries

Abstract: A detailed study and further development of the capillary model for charged wide-pore membranes is presented. Previous work on this model has either linearized the Poisson–Boltzmann equation and/or assumed a small Debye length-to-tube-radius ratio, or ignored axial concentration gradients. None of these simplifications are made here. The problem is characterized by a set of nine coefficients coupling the various transport phenomena. We establish these coefficients and combine them to form “figures of merit” wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
270
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(279 citation statements)
references
References 6 publications
6
270
1
2
Order By: Relevance
“…Charged capillary nanopores and nanotubes are essential in many natural and technological systems, as part of porous membranes separating two aqueous electrolytes [1][2][3][4][5][6][7][8][9][10][11][12][13]. Membranes containing charged nanopores can be used for water desalination, selective ion removal, and electrokinetic energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Charged capillary nanopores and nanotubes are essential in many natural and technological systems, as part of porous membranes separating two aqueous electrolytes [1][2][3][4][5][6][7][8][9][10][11][12][13]. Membranes containing charged nanopores can be used for water desalination, selective ion removal, and electrokinetic energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The radial variation of potential and ion concentrations in the pore as well as the impact of electroosmotic flow on ion transfer are taken into account in the space-charge (SC) model, which was originally developed in [20]. Detailed comparison between results obtained from SC and TMS models [21] showed a good agreement for pores with small radius (less than 2 nm) and low surface charge density.…”
Section: Introductionmentioning
confidence: 71%
“…Figure 3 shows the dependence of residuals R for continuity equation (18) or (25) and negative ion transport equation (20) or (27) on the number of iterations n. One can see that the use of Slotboom variables allows to decrease the required number of iterations by 2-3 times in comparison with the use of Primitive variables. The Coupled method allows to decrease this number further by 5 times.…”
Section: Numerical Implementationmentioning
confidence: 97%
“…We have performed a comparison of convergence between formulations in Primitive variables (3)- (5) and Slotboom variables (10)- (12). It was found that the use of Slotboom variables allows to decrease the required number of iterations by 2 times.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…The radial variation of potential and ion concentrations in the pore as well as the impact of electroosmotic flow on ion transfer are taken into account in the space-charge (SC) model, which was originally developed in [12]. Experimental verification of this model was performed by comparing the theoretical predictions for streaming potential, pore conductivity, and diffusion potential with the measured data [13].…”
Section: Introductionmentioning
confidence: 99%